Cajanol Sensitizes A2780/Taxol Cells to Paclitaxel by Inhibiting the PI3K/Akt/NF-κB Signaling Pathway - Sui, Ming; Yang, Hairong; Guo, Mingqi; Li, Wenle; Gong, Zheng; Jiang, Jing; Li, Peiling (Frontiers in Pharmacology, 2021)
Ovarian cancer is the second most common gynecological malignancy, and one of the most deadly. The bottleneck restricting the treatment of ovarian cancer is its MDR to chemotherapy. Cajanol is an isoflavone from pigeon pea (Cajanus cajan) that has been reported to have anti-tumor activity. In this work, we evaluate the effect of cajanol in reversing paclitaxel resistance of the A2780/Taxol ovarian cancer cell line in vitro and in vivo, and we discuss its mechanism of action. We found that 8 μM cajanol significantly restored the sensitivity of A2780/Taxol cells to paclitaxel, and in vivo experiments demonstrated that the combination of 0.5 μM/kg paclitaxel and 2 μM/kg cajanol significantly inhibited the growth of A2780/Taxol metastatic tumors in mice. Flow cytometry, fluorescence quantitative PCR, western blotting and other methods were used to study the mechanism of reversing paclitaxel resistance with cajanol. First, we determined that cajanol inhibits paclitaxel efflux in A2780/Taxol cells by down-regulating permeability glycoprotein (P-gp) expression, and further found that cajanol can inhibit P-gp transcription and translation through the PI3K/Akt/NF-κB pathway. The results of this work are expected to provide a new candidate compound for the development of paclitaxel sensitizers.